AB0765 Secukinumab provides sustained improvement in function, quality of life and fatigue over 2 years in patients who achieved disease activity index for psoriatic arthritis (DAPSA) remission. (15th June 2017) - Smolen, JS; McInnes, IB; Gossec, L; Strand, V; Pricop, L; Fox, T; Jugl, S; Gaillez, C; ,
Abstract : Background: Disease Activity index for Psoriatic Arthritis (DAPSA) states are associated with functional impairment levels in patients (pts) with psoriatic arthritis (PsA). 1 Secukinumab demonstrated sustained improvements in disease activity assessed with DAS28-CRP, physical function and pt-reported outcomes (PROs) among active PsA pts over 104 weeks (wks) in the FUTURE 2 study. 2 Objectives: To explore the relationship between DAPSA states and function, health-related quality of life and PROs, and the individual DAPSA components in the different states in pts treated with secukinumab through 104 wks using post-hoc analysis. Methods: FUTURE 2 study design has been reported. 3 DAPSA was derived as sum of five core components: tender joint and swollen joint counts (TJC 68, SJC 66), pt global assessment (PtGA) and pain (PP) assessed by a 10cm VAS and CRP (mg/dl). Four DAPSA states were: remission (REM:≤4), low (LDA:>4–≤14), moderate (MDA:>14–≤28) or high disease activity (HDA:>28). Mean±SD of each core component of DAPSA were analysed at Wks 16, 24, 52 and 104 using observed data. The relationship between HAQ-DI, SF-36 PCS and MCS, PsAQoL, DLQI and FACIT-Fatigue with DAPSA states was assessed in the pooled treatment arms at each time point using a mixed-effect model for repeated measures (MMRM) analyses. Results: Baseline characteristics were similar across treatment groups. 3 DAPSA scores at baseline (mean±SD) were 42.0±17.4, 46.8±24.3 and 44.9±25.3 in the secukinumab 300mg, 150mg and placebo groups, respectively. Mean scores of each component by DAPSA states at Wk 16 are shown in table and were sustained through Wk 104. Significant differences were observed among secukinumab treated pts between REM vs. HDA and LDA vs. HDA states for PRO scores through Wk104 (Figure). Conclusions: In pts treated with secukinumab 300 or 150mg, the five individual components related to DAPSA REM were <1 in contrast with other disease states and were sustained through Wk 104. DAPSA REM was associated with significantly greater improvement in physical function, health related quality of life and fatigue indicating that it is an important target to be achieved and sustained in PsA pts. References: Schoels MM, et al. Ann Rheum Dis 2016;75:811–8. McInnes IB, et al. Arthritis Rheumatol 2016;68(suppl 10). McInnes IB, et al. Lancet 2015;386:1137–46. Disclosure of Interest: J. Smolen Grant/research support from: AbbVie, Janssen, Eli Lilly, MSD, Pfizer, Roche, Amgen, AstraZeneca, Astro, Celgene, Celltrion, GSK, ILTOO, Medimmune, Novartis-Sandoz, Pfizer, Samsung, Sanofi and UCB., Consultant for: AbbVie, Janssen, Eli Lilly, MSD, Pfizer, Roche, Amgen, AstraZeneca, Astro, Celgene, Celltrion, GSK, ILTOO, Medimmune, Novartis-Sandoz, Pfizer, Samsung, Sanofi and UCB., I. McInnes Grant/research support from: AbbVie, Amgen, BMS, Celgene, Janssen, Lilly, Novartis, Pfizer and UCB, Consultant for: AbbVie, Amgen, BMS, Celgene, Janssen, Lilly, Novartis, Pfizer and UCB, L. Gossec Grant/research support from: UCB, Eli Lilly and Pfizer; Consultant for AbbVie, BMS, Celgene, Janssen, Novartis, Pfizer and Roche, V. Strand Consultant for: AbbVie, Amgen, BMS, Celgene, Celltrion, Corrona, Genentech/Roche, GSK, Janssen, Lilly, Merck, Novartis, Pfizer, Regeneron, Samsung, Sanofi and UCB, L. Pricop Shareholder of: Novartis, Employee of: Novartis, T. Fox Shareholder of: Novartis, Employee of: Novartis, S. Jugl Shareholder of: Novartis, Employee of: Novartis, C. Gaillez Shareholder of: Novartis and BMS, Employee of: Novartis